The ethics of social punishment : the enforcement of morality in everyday life - Radzik, Linda, 1970-; Bennett, Christopher, 1972-; Pettigrove, Glen.; Sher, George (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
""This volume makes social punishment the central category of analysis. The philosophical literature on punishment is so wholly concentrated on the state's responses to crime that authors sometimes dismiss talk of punishment in everyday life as merely metaphorical. But this is mistaken. Legal norms are not the only ones that society enforces and the mechanisms of law are not the only methods of enforcement that society uses. This work argues that at least many instances of rebuke, social withdrawal, boycotting, and public shaming should be interpreted as cases of punishment. It argues that the general justifying aim of informal social punishments, such as these, is to morally pressure wrongdoers to make amends. Yet the legitimacy of using social punishment also turns on the tension between individual desert and social good, as well as the possession of an authority to punish".
Includes bibliographical references and index.
Keywords: Social acceptance -- Moral and ethical aspects; Social isolation; Punishment -- Social aspects; Judgment (Ethics)